TV-Satellite Image Quality Evaluation by Cross-Correlation - Al-Zuky, Ali A D; Ali, Esraa H (Al-Nahrain Journal of Science, 2018)
Cross-Correlation is widely used to match images. In this work, an attempt is made to study the cross-correlation performance on the TV-satellite images. These images were taken from a channel (Abu Dhabi) broadcasts over three satellites (Arabsat, Hotbird, and Nilesat). The aim of this work is to determine the best quality TV-Satellite images on one satellite and compare it with the other satellites. It has been considered the automatic selected regions based on searching for the region that has minimum standard deviation of luminance (σminL) in the image. The cross-correlation method was computed for the found σminL block and the block next to it by one pixel. In this method all RGB-L components are calculated. The results indicated that the image on the Nilesat was correlated more than the images on the other satellites.